Data from: Spatial contraction of demersal fish populations in a large marine ecosystem - Orio, Alessandro; Bergström, Ulf; Florin, Ann-Britt; Lehmann, Andreas; Šics, Ivo; Casini, Michele (Dryad, 2019)
Aim: The interdependencies between trophic interactions, environmental factors and anthropogenic forcing determine how species distributions change over time. Large changes in species distributions have occurred as a result of climate change. The objective of this study was to analyse how the spatial distribution of cod and flounder have changed in the Baltic Sea during the past four decades characterized by large hydrological changes. Location: Baltic Sea Taxon: Cod (Gadus morhua) and flounder (Platichthys flesus) Methods: Catch per unit of effort (CPUE) data for adult and juvenile cod and for adult flounder were modelled using Delta-Generalized additive models including environmental and geographical variables between 1979 and 2016. From the annual CPUE predictions for each species, yearly distribution maps and depth distribution curves were obtained. Mean depth and the depth range were estimated to provide an indication on preferred depth and habitat occupancy. Results: Adult and juvenile cod showed a contraction in their distribution in the southern areas of the Baltic Sea. Flounder, instead, showed an expansion in its distribution with an increase in abundance in the northern areas. The depth distributions showed a progressive shift of the mean depth of occurrence towards shallower waters for adult cod and flounder and towards deeper waters for juvenile cod, as well as a contraction of the species depth ranges, evident mainly from the late 1980s. Main conclusions: Our study illustrates large changes in the spatial distribution of cod and flounder in the Baltic Sea. The changes in depth distribution occurred from the late 1980s are probably due to a combination of expanded areas of hypoxia in deep waters and an increase in predation risk in shallow waters. The net effect of these changes is an increased spatial overlap between life stages and species, which may amplify cod cannibalism and the interaction strength between cod and flounder. Data_cod_flounderAdult cod, juvenile cod and flounder CPUE data (in ...